(untitled) (Journal of Management and Social Sciences, 2026)
Migration is one of the oldest and most vexed issues globally. Migration has become a crucial subject in recent times especially in context of identity, intra-Africa migration and development. It is against this background that AU Agenda 2063 becomes relevant. Extant studies and instruments have explored diverse issues on migration, intra-Africa migration, colonialism, forced migration, migration and remittances, migration and development, and migration and identity. This is especially so within the framework of the AU and ECOWAS. However, a common thread running through all these studies, reports and instruments is the treatment of migration generically, with emphasis on its socioeconomic and political importance. Anchored on secondary method of data collection and the Ubuntu philosophy of communalism and interconnectedness, this article offers a decolonial perspective of ethical and philosophical notion of identity, intra-Africa migration and development within the framework of AU Agenda 2063. Findings suggest that the success of AU Agenda 2063 on identity, intra-Africa migration and integration will depend not on the complexity of its governance instruments, but on its ability to re-anchor the issues on African philosophy and ethical traditions which construct identity, intra-Africa migration and development and narrate them in contexts of African social relations, mutual collectiveness, existential interdependence and social belonging. Keywords Identity, intra-Africa migration, African Union, AU Agenda 2063, decolonial perspective